Prevalence of overweight/obesity among medical students at Suraram, India - Dumpala, Suguna; Chadaram, Balakrishna; Berad, Aditya (International Journal Of Community Medicine And Public Health, 2018)
Background: Overweight/obesity is a critical public health problem in both developed and developing nations, has nearly tripled since 1975. In 2016, more than 1.9 B were overweight and 650 M obese. Studies from different parts of India have reported a rise in prevalence of obesity (11 to 37.5%). To date, there are not many studies on the prevalence of obesity among medical students in India. Hence this study was conducted with an objective to assess the prevalence of overweight/obesity and its associated factors among young medical students. Methods: VI Semester MBBS students of the year 2013 batch of Malla Reddy Medical College for Women were interviewed in March and April 2016. Results: Out of 150 participants, 125 responded (83%). Overall prevalence of obesity/overweight was 45%. Mean age of the sample was 20 years (±0.75); more belonged to upper than lower strata (61.6% vs. 38.4%); 86.4% were from nuclear family, means better food and care. Chi-squared test revealed significant differences for age, higher socio-economic status, diet, physical inactivity and co-morbidities associated with obesity/overweight (p<0.05). There was significant positive correlation values between BMI and waist circumference at p<0.01 level. The correlation of BMI with waist circumference is (r=0.675). Conclusions: It is crucial to establish cost-effective strategies like promotion of healthy foods, introducing extra-curricular activities at institutional level, avoiding junk food are likely to have a major effect in reducing obesity among these young medicos. This would also enable them to maintain normal weights, avoid immediate and long-term complications associated with overweight/obesity.